2018
DOI: 10.1051/0004-6361/201731855
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Imaging of Transiting Extrasolar Planetary systems (HITEP)

Abstract: Context. The formation and dynamical history of hot Jupiters is currently debated, with wide stellar binaries having been suggested as a potential formation pathway. Additionally, contaminating light from both binary companions and unassociated stars can significantly bias the results of planet characterisation studies, but can be corrected for if the properties of the contaminating star are known. Aim. We search for binary companions to known transiting exoplanet host stars, in order to determine the multipli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(70 citation statements)
references
References 103 publications
7
62
0
Order By: Relevance
“…This enhancement can be caused by the secondary inducing spiral density waves in the protoplanetary disc, which can potentially stimulate gravitational instability (GI) (Batygin et al 2011;Rafikov 2013). This is in line with observations that suggest a 3-fold increase in hot Jupiter occurrence in binary stars compared to singles (Wang et al 2015;Ngo et al 2016;Evans et al 2018;Fontanive et al 2019). Binary stars should thus be taken into consideration when analysing planet formation and evolution, not only because binary stars represent ∼ 1/3 of stars in the Milky Way (M: 26.8% ± 1.4% Winters et al (2019), FGK: 33% ± 2% Raghavan et al (2010), A: 32.1 +3.9 −3.5 % De Rosa et al (2014)), but also to understand the robustness and diversity of planet formation.…”
Section: Introductionsupporting
confidence: 76%
“…This enhancement can be caused by the secondary inducing spiral density waves in the protoplanetary disc, which can potentially stimulate gravitational instability (GI) (Batygin et al 2011;Rafikov 2013). This is in line with observations that suggest a 3-fold increase in hot Jupiter occurrence in binary stars compared to singles (Wang et al 2015;Ngo et al 2016;Evans et al 2018;Fontanive et al 2019). Binary stars should thus be taken into consideration when analysing planet formation and evolution, not only because binary stars represent ∼ 1/3 of stars in the Milky Way (M: 26.8% ± 1.4% Winters et al (2019), FGK: 33% ± 2% Raghavan et al (2010), A: 32.1 +3.9 −3.5 % De Rosa et al (2014)), but also to understand the robustness and diversity of planet formation.…”
Section: Introductionsupporting
confidence: 76%
“…Evans et al (2016a) carried out an additional high-resolution imaging campaign, and they determined a common proper motion with 2σ significance. An additional companion to the system that was also detected by Evans et al (2016a) was ruled out at a later stage and identified as an instrumental artefact (Evans et al 2018). Therefore, previous studies have presented much evidence that HAT-P-41 is indeed a binary system.…”
Section: Hat-p-41mentioning
confidence: 82%
“…0950, which is unfortunately outside the IRDIS field of view. The potential companion, however, was picked up by Gaia DR2, and together with two additional sources listed that were previously considered unlikely to be bound by Evans et al (2018), these three objects were clearly proven to be background based on their parallaxes.…”
Section: K2-38mentioning
confidence: 93%
“…WASP-70 is the system with the second-brightest nearby companion, with ∆K = 1.38 ± 0.18 mag and a separation of 3.2 . The companion was detected in the discovery paper of the system (Anderson et al 2014) and in subsequent Lucky Imaging (Wöllert & Brandner 2015;Ginski et al 2016;Evans et al 2018) and adaptive-optics (Ngo et al 2016) studies. In Paper I we established that its proper motion is consistent with it being a bound, not background, object.…”
Section: Wasp-70mentioning
confidence: 98%